Artificial Intelligence Platforms – A New Research Agenda for Digital Platform Economy - Tomasz Mucha; Timo Seppälä (The Research Institute of the Finnish Economy (ETLA), 2020)
Three out of nine of S&P500 digital platform companies stand out as building own artificial intelligence (AI) platforms. There is overwhelming empirical evidence of AI technologies are being central to running a digital platform business. However, the current research agenda is not directing researchers to study AI technologies in the context of digital platforms. We have divided the proposed AI platforms research agenda as follows: The first set of questions we propose relates to an overall conceptualization of AI platforms. Thereafter, we recognize specific aspects of AI platforms, which need to be investigated in detail to gain understanding that is more complete. The second set of questions we propose relates to understanding the dynamics between AI platforms and the broader socio-economic context. This topic might be particularly relevant to economies of countries without indigenous AI platforms. Our paper builds on the proposition that AI is a general-purpose technology, which by itself carries properties of a digital platform.
Keywords: M1; M21; O3; O33; 330; Platforms; Digital Platform Economy; Artificial Intelligence; AI platforms; Research agenda